Antibacterial Activity and Phytochemical Analysis of Geranium homeanum Turez Leaves - Fri Rahmawati; Maria Bintang; I Made Artika (IPB University, 2017)
Geranium homeanum Turez is a herbaceous plant used as an empirical medicine. This research was carried out to test the antibacterial activity and determine minimum inhibition concentration (MIC) to Staphylococcus aureus and Pseudomonas aeruginosa with agar diffution method and phytochemical analysis of geranium leaves by Harbone method. The young and old geranium leaves were blended then filtrated. The obtained filtrate was divided into two parts, one part heated by autoclave and the other was unheated. Each filtrate was tested against to Staphylococcus aureus and Pseudomonas aeruginosa. Geranium leaves filtrate having the highest antibacterial activity was heated at 500C until it become dry powder. The powder was used to measure MIC and phytochemical analysis.The results showed that the antibacterial activity of young leaves filtrate was higher than the old leaves filtrat, and the unheated leaves filtrate was higher than heated filtrate one. MIC of S. aureus and P. aeruginosa, were as follows 15 mg/ml and 20 mg/mL respectively. The antibacterial activity of powder geranium’s leaves filtrate was weaker than 100 µg/mL ampicilline. Phytochemical analysis of geranium leaves showed positive contents of alkaloid and triterpenoid.